HUBUNGAN EFIKASI DIRI TERHADAP PRESTASI BELAJAR SISWA KELAS XI MIPA SMA NEGERI 5 MODEL PALU: The Relationship Between Self-Efficacy and Learning Achivement of Students in Class XI MIPA SMA Negeri 5 Model Palu - Abdurahman, Algyfahri S.; Hadjar, Ibnu (Universitas Tadulako, 2025)
This study aims to determine the relationship between self-efficacy and learning success of students in class XI MIPA at SMA Negeri 5 Palu Model in the 2023/2024 academic year. This research uses a quantitative approach. This type of research is ex post facto. This research was conducted in class XI MIPA SMA Negeri 5 Palu model. This study used a sample size of 98 out of 224 students. Sampling was done using random sampling technique. Data were collected using self-efficacy scale and students' report card scores in odd semester. This analysis method uses descriptive statistics, and the relationship between two variables, namely self-efficacy to student learning achievement, is determined by calculating using product-moment correlation. The results showed that there was a relationship between self-efficacy and learning achievement of 11th grade students of SMA Negeri 5 Model Palu.